Video Pembelajaran untuk Meningkatkan Keterampilan Membaca Permulaan pada Pelajaran Bahasa Indonesia - Viqi Izzatul Muhlisoh; I Gede Wawan Sudatha; Kadek Yudiana (Universitas Pendidikan Ganesha, 2022)
The value of the Indonesian test still needs to be revised. Many also found that elementary school students still could not read and were not fluent in reading. This study aims to develop learning videos to improve early reading skills in Indonesian language learning in first-grade elementary school. This type of research is the development of the ADDIE model. The research subjects were two material experts, two design experts, and two media experts. The test subjects were two practitioners and 35 students. Methods of data collection by interview, observation, and questionnaires. Rating scale research instrument. The technique of analyzing the data is descriptive qualitative and quantitative analysis. The results of the study are the results of expert assessment of material validity 91% (very good), media experts 89% (good), and design experts 90.5% (very good). The practitioner's response test results were 97% (very good), and the student's response was 95.6% (very good). It was concluded that the video got very good validity and deserved to be used. The research implication is that this video can be used to help students learn to read.